Exploring translation strategies for Chinese dialogue and buzzwords based on 星星上的花（The Flower on the Stars） - Wan, Wenyi (Nanyang Technological University, 2021)
In this project, through translating excerpts from a Chinese novel, I identify several problems that can affect the translation work of literary texts, especially contemporary literary texts. I try to deal with these problems in translation practice by combining relevant theoretical knowledge, hoping to provide some reference for subsequent translation. During the translation process, two main problems are found: on the one hand, the problem concerning the grasp of language style and register, and the corresponding problem of how to choose words in the face of diverse texts; on the other hand, the problem of how to translate Chinese buzzwords in English. It is necessary to solve those two problems and the solutions can be very helpful in the future. This project combines linguistic and cultural theories, and adopts the methods of theoretical analysis, comparative argumentation, and case study. By making excerpts of important plots from a famous Chinese novel and completing a 10,000-word translation from Chinese to English, two major aspects are identified and divided into multiple parts for analysis and commentary. By citing the relevant theories of pragmatics, I analyze the speech acts of the characters when the objects and situations are different and explain the diction of the translation. In addition, I explain the translation strategies for buzzwords from many perspectives. In general, the two major problems found in this project have been dealt with and answered in a more complete way. For texts with more dialogue, the translation can be analyzed from the perspective of pragmatics, which can better help the translator understand the original text and make wording choices; for texts with more buzzwords, the translation can be freely handled so that the readers of the translated language can better enjoy the essence of the original work.